Analysis of in-season external load and sport performance in women's collegiate basketball - Brown, F. S. A.; Fields, J. B.; Jagim, A. R.; Baker, R. E.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2024)
Quantifying and monitoring athlete workload throughout a competitive season is a means to manage player readiness. Therefore, the purpose of the current study was to quantify practice and game external loads and to assess the relationship between such loads and basketball-specific performance metrics across a women's collegiate basketball season. Thirteen National Collegiate Athletic Association Division I women basketball athletes (age 20.08 ± 1.55 years) wore Global Positioning Systems sensors equipped with triaxial accelerometers for 29 games and 66 practices during the 2019-20 season. A multivariate analysis of variance was used to assess differences in external load between high- and low-minute players and across quarters within games (p < 0.05). Bivariate Pearson correlation coefficients were run to determine relationships between external loads and metrics of basketball performance. Findings indicated that high- and low-minute athletes experienced different loads during games and practices (p < 0.001). External loads differed by quarter, such that player load (PL) was highest in Q4 (p = 0.007), PL·min-1 was highest in Q1 and lowest in Q4 (p < 0.001), and explosive ratio (i.e., ratio of PL and explosive efforts) was lowest in Q3 (p = 0.45). Relationships existed between PL·min-1 and field goals (r = 0.41; p = 0.02) and between the explosive ratio and free throws (r = 0.377 p = 0.04). These results can be used to inform design of training sessions with the intent to prepare athletes for the demands of the competitive season. It is recommended that future research continue to explore the relationship of sport-specific performance metrics and athlete external load.